INTERNATIONAL ELECTORAL STANDARDS AND ELECTORAL LAW OF SUBJECTS OF THE RUSSIAN FEDERATION - D. B. Sergeev (Scientific Journal of Pedagogy and Economics, 2019)
Research objective is the legal research of the international electoral standards applied at legal regulation of elections to public authorities of subjects of the Russian Federation. The analysis, synthesis and legal method are applied. Contents of the Constitution of the Russian Federation, regarding use of rules of international law, international legal acts, including selective (Universal Declaration of Human Rights, International Covenant on Civil and Political Rights, Document of the Copenhagen meeting of the Conference on human measurement of CSCE, Convention on protection of Human Rights and Fundamental Freedoms and Convention on standards of democratic elections, electoral rights and freedoms in the State Parties of the CIS), decisions of the Constitutional Court of the Russian Federation and the Russian common courts in which these bodies applied electoral laws, decisions on electoral disputes of European Court of Human Rights and works of scientists are studied. The author analyzes the ideas that in electoral law of subjects of the Russian Federation it is difficult to find consequences of application of the international electoral standards and comes to a conclusion that as this standards are the principles, the provided statement is exaggerated.